Could the production region influence the quality and antioxidant activity of cashew apple? (2022)
Given the scarcity of research related to the interference of the climatic elements under the qualitative characteristics of the cashew apples, this work had the objective of evaluating the quality and total antioxidant activity of cashew apple of dwarf cashew in different climatic conditions. The experimental design was completely randomized, in a factorial scheme with repeated measurement in time, with three clones (CCP 09, BRS 265 and PRO 555-1) in two regions, cearense semiarid, sertão (Alto Santo – CE) and a coast (Beberibe – CE), with four replications and evaluated in different years. In the laboratory, the fruits were processed to obtain the pulp and evaluated for: soluble solids (SS, °Brix), titratable acidity (TA, % malic acid), SS/TA, soluble sugars (AS, % glucose), vitamin C (mg/100 g), total extractable polyphenols (TEP, mg L-1), cinnamic acid (CA, mg L-1), transcinnamoyl glycoside (TG, mg L-1) and total antioxidant activity (TAA, μmol Trolox/g). It was observed highest values of SS, TA, AS, vitamin C, TG, TEP and TAA obtained in cashew apple in the sertão. The ‘CCP 09’ showed higher quality to the others, responding in a positive way to the variations of environments conditions. The quality and antioxidant activity of cashew apple are influenced by the climatic elements of each region, as well as the year of production and the genotype. The antioxidant activity attributed to the cashew apple showed to be more strongly related to TEP and transcinnamoyl glycoside content.